Factors associated with COVID-19 vaccination in medical students from a Peruvian university - Dextre-Vilchez, Sergio Armando (2022)
Objective: To determine the factors associated with COVID-19 vaccination in medical students from Universidad Peruana Los Andes. Materials and methods: An observational, analytical and cross-sectional study. A total of 243 second- to tenth-academic term students completed a questionnaire about sociodemographic and academic characteristics, family and personal medical history, and the number of COVID-19 vaccine doses received. To determine the association, chi-square test and Student’s t-test were used. Results: Vaccination coverage was 98.77 %, out of which 61.73 % had three doses. In addition, 46.50 % of the students reported having been infected with COVID-19 at least once. The bivariate analysis showed that age (p = 0.047) and place of residence (p = 0.042) were significantly associated with the vaccination status. Conclusions: Although vaccination coverage was very high, it should be noted that a great number of students did not receive booster doses. The associated factors were age and place of residence. It is recommended to encourage vaccination in students due to the proximity of the return to in-person classes and its influence on public opinion.